2013
DOI: 10.1105/tpc.113.118042
|View full text |Cite
|
Sign up to set email alerts
|

Replication Protein A2c Coupled with Replication Protein A1c Regulates Crossover Formation during Meiosis in Rice    

Abstract: Replication protein A (RPA) is a conserved heterotrimeric protein complex comprising RPA1, RPA2, and RPA3 subunits involved in multiple DNA metabolism pathways attributable to its single-stranded DNA binding property. Unlike other species possessing a single RPA2 gene, rice (Oryza sativa) possesses three RPA2 paralogs, but their functions remain unclear. In this study, we identified RPA2c, a rice gene preferentially expressed during meiosis. A T-DNA insertional mutant (rpa2c) exhibited reduced bivalent formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 63 publications
(80 reference statements)
1
16
0
Order By: Relevance
“…DSB formation is the first step in meiotic recombination and in rice can be assayed indirectly by detection of phosphorylated gH2AX (Mahadevaiah et al, 2001;Che et al, 2011). OsCOM1 and RPA2c are required for DSB end-processing and 39-single-strand invasion after DSB generation (Ji et al, 2012;Li et al, 2013) and DMC1 and RAD51C indicate the number of potential strand invasion events (Neale and Keeney, 2006;Tang et al, 2014). Our analysis showed that the localization of gH2AX, OsCOM1, RPA2c, DMC1, and RAD51C in osgen1 was indistinguishable to wild-type male meiocytes (Fig.…”
Section: Osgen1 Is Dispensable For Formation Of Synaptonemal Complex mentioning
confidence: 72%
See 1 more Smart Citation
“…DSB formation is the first step in meiotic recombination and in rice can be assayed indirectly by detection of phosphorylated gH2AX (Mahadevaiah et al, 2001;Che et al, 2011). OsCOM1 and RPA2c are required for DSB end-processing and 39-single-strand invasion after DSB generation (Ji et al, 2012;Li et al, 2013) and DMC1 and RAD51C indicate the number of potential strand invasion events (Neale and Keeney, 2006;Tang et al, 2014). Our analysis showed that the localization of gH2AX, OsCOM1, RPA2c, DMC1, and RAD51C in osgen1 was indistinguishable to wild-type male meiocytes (Fig.…”
Section: Osgen1 Is Dispensable For Formation Of Synaptonemal Complex mentioning
confidence: 72%
“…The polyclonal antibodies OsREC8, PAIR2, PAIR3, ZEP1, gH2AX, OsCOM1, RAD51C, and HEI10 used in this study were prepared according to Wang et al (2009Wang et al ( , 2010Wang et al ( , 2011Wang et al ( , 2012, Ji et al (2012), Miao et al (2013), and Tang et al (2014). The antibody against RPA2c was described in Li et al (2013). Antib-tubulin antibody was obtained from Sigma-Aldrich (catalog no.…”
Section: Antibody Productionmentioning
confidence: 99%
“…Arabidopsis and Oryza possess multiple paralogs of the replication protein A (RPA) complex subunits and several rpa mutant alleles have been shown to specifically reduce class I crossovers, whereas overall DSB repair remains efficient (Osman et al 2009;Li et al 2013). In budding yeast, meiotic DSB repair shows a general dependence on RPA (Soustelle et al 2002), but RPA phosphorylation modulates crossover patterning (Bartrand et al 2006).…”
Section: Recombination-associated Dna Synthesismentioning
confidence: 99%
“…Compared to the large chromosomes of the cereal crops, rice (Oryza sativa) has a larger number of relatively small chromosomes (2n=2x=24) and a small genome ~420 Mb (14). However, during meiosis, wild-type metaphase I chromosome spreads revealed that bivalents consisted of a mixture of rods and rings with chiasma location biased towards the ends of chromosomes (59,92). The chiasma frequency and distribution was dramatically altered in a mutant of the rice synaptonemal complex transverse filament protein ZEP1 (92).…”
Section: Chiasma Localization In Members Of the Grass Familymentioning
confidence: 99%